The Impact of Customer Relationship Management on Customer Loyalty with Customer Satisfaction as a Mediating Variable at Telkomsel Partner Outlets in Banjar City - Mochamad Arif Rachman; Maya Ariyanti (Goodwood Publishing, 2025)
Purpose: The internet's rise has made fast communication essential. This study explores how Telkomsel's CRM affects customer satisfaction, with loyalty as a mediating factor at partner outlets in Banjar City. Research methodology: This quantitative study involved 145 purposively selected respondents and used SEM-PLS for data analysis. Results show that CRM positively affects customer satisfaction and lo yalty, with satisfaction also mediating the CRM–loyalty relationship. Results: These results indicate the importance of CRM strategies in fostering long-term customer loyalty by enhancing satisfaction through personalized and responsive services. The study highlights the need for Telkomsel and similar companies to continually invest in CRM technologies and strategies to adapt to evolving customer needs and maintain a competitive edge in the telecommunications industry. alignment with user needs and characteristics. Conslusion: CRM significantly enhances customer satisfaction and loyalty. Satisfaction also mediates the relationship between CRM and loyalty, highlighting the need for responsive and personalized services. Limitation: The study is limited to Telkomsel outlets in Banjar City and uses purposive sampling, reducing generalizability. Other factors like service quality or brand trust were not examined. Contribution: This study confirms the mediating role of satisfaction in CRM–loyalty links and offers practical insights for improving CRM strategies in the telecom sector.